The Doppler shock index measured by a wearable ultrasound patch accurately detects moderate‐to‐severe central hypovolemia during lower body negative pressure. Issue 4 (7th August 2021) - Kenny, Jon‐Émile S.; Elfarnawany, Mai; Yang, Zhen; Myers, Matt; Eibl, Andrew M.; Eibl, Joseph K.; Taylor, Jenna L.; Kim, Chul Ho; Johnson, Bruce D.
Abstract: Objective: Moderate‐to‐severe hemorrhage is a life‐threatening condition, which is challenging to detect in a timely fashion using traditional vital signs because of the human body's robust physiologic compensatory mechanisms. Measuring and trending blood flow could improve diagnosis of clinically significant exsanguination. A lightweight, wireless, wearable Doppler ultrasound patch that captures and trends blood flow velocity could enhance hemorrhage detection. Methods: In 11 healthy volunteers undergoing simulated hemorrhage and resuscitation during graded lower body negative pressure (LBNP) and release, we studied the relationship between stroke volume (SV) and common carotid artery velocity time integral (VTI) and corrected flow time (FTc). We assessed the diagnostic accuracy of 2 variations of a novel metric, the Doppler shock index (ie, the DSIVTI and DSIFTc ), at capturing moderate‐to‐severe central hypovolemia defined as a 30% reduction in SV. The DSIVTI and DSIFTc are calculated as the heart rate divided by either the VTI or FTc, respectively. Results: A total of 17, 822 cardiac cycles were analyzed across 22 LBNP protocols. The average SV reduction to the lowest tolerated LBNP stage was 40%; there was no clinically significant fall in the mean arterial pressure. Correlations between changing SV and the common carotid artery VTI and FTc were strong ( R 2 of 0.87, respectively) and concordant. The DSIVTI and DSIFTc accurately detected moderate‐to‐severe central hypovolemia with values for the area under the receiver operator curves of 0.96 and 0.97, respectively. Conclusion: In a human model of hemorrhage and resuscitation, measures from a wearable Doppler ultrasound patch correlated strongly with SV and identified moderate‐to‐severe central hypovolemia with excellent diagnostic accuracy.